2017
DOI: 10.1038/emi.2017.13
|View full text |Cite
|
Sign up to set email alerts
|

Full genetic characterization and epidemiology of a novel amdoparvovirus in striped skunk (Mephitis mephitis)

Abstract: Amdoparvovirus is a newly defined parvoviral genus that contains four species (Carnivore amdoparvovirus 1–4), including the well-known Aleutian mink disease virus (AMDV). Amdoparvoviruses cause an immune-associated and often lethal wasting syndrome in Mustelidae and Caninae hosts. In this study, we molecularly investigated amdoparvoviruses detected in 44 striped skunks (Mephitis mephitis) found dead in and around Vancouver, British Columbia, Canada. Some of the animals exhibited pathological changes compatible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 38 publications
2
47
0
1
Order By: Relevance
“…Antibodies to ADV have been documented in other marten species (Fournier‐Chambrillon et al, ) and in experimentally infected fishers. SKAV was also found in a mink, suggesting it displays some host promiscuity, as does ADV (Canuti et al, ). Shifts of only a few amino acids in parvoviruses, including ADV, can shift viral tropism (Tijssen, ) in turn allowing transmission to naïve species.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Antibodies to ADV have been documented in other marten species (Fournier‐Chambrillon et al, ) and in experimentally infected fishers. SKAV was also found in a mink, suggesting it displays some host promiscuity, as does ADV (Canuti et al, ). Shifts of only a few amino acids in parvoviruses, including ADV, can shift viral tropism (Tijssen, ) in turn allowing transmission to naïve species.…”
Section: Discussionmentioning
confidence: 98%
“…Further sequencing of the full genome would be helpful. It has been suggested that all published genetic material from amdoparvoviruses in skunks falls within SKAV regardless of whether it was identified initially as ADV (Canuti et al, ). Overall, our data are consistent with SKAV having long been present but undetected in striped skunks in California.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently circulating AMDV strains probably originated in North America, but viruses have been diffused worldwide as a consequence of international animal trading and similar viral strains now circulate on farms and surrounding areas around the world [18,21,22]. Furthermore, other viruses within the genus Amdoparvovirus have recently been discovered that can infect related carnivores, such as skunk amdoparvovirus (SKAV), red panda amdoparvovirus (RpAPV), raccoon dog and fox amdoparvovirus (RFAV), gray fox amdovirus (GFAV) and red fox fecal amdovirus (RFFAV) [23][24][25][26][27]. Because these viruses replicate in macrophages and viral entry is likely mediated by cellular Fc receptors recognizing antibody covered viral particles, cross-species transmission is common [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in DNA sequencing technology led to the identification of four novel Amdoparvoviral species, igniting new studies of molecular pathogenesis and epidemiology [31,32]. Dr. Marta Canuti (Memorial University of Newfoundland) presented studies of AMDV molecular epidemiology in farmed and wild animals in Newfoundland, and contrasted this data with worldwide AMDV phylogeography and evolution.…”
Section: Driving Forces For Aleutian Mink Disease Virus Evolutionmentioning
confidence: 99%